Making Holing Machine for AC Connecting Tube Product K25G - Antonius Adi Soetopo; Suseno Suseno (Yayasan Banu Haji Samsudin, 2025)
Holing Machine is an after pressing tool that functions to make holes in the product. This Holing Machine is specifically used to make holes in the Tube AC ​​Connecting K25G product that has finished the pressing process. The after pressing process of making holes in the Tube AC ​​Connecting K25G product was previously done manually with the help of marking and Air Grinder. This method takes quite a long time, which is about 8 minutes to make holes in 4 Tube AC ​​Connecting K25G products, resulting in wasted production time. This led to the creation of a Holing Machine to help the process of making holes in the Tube AC ​​Connecting K25G product so that it can be done automatically. The Holing Machine is made with several stages of the manufacturing process starting with the process of making machine construction drawings, the process of selecting and preparing materials by the company, the machining process for making parts, the part assembly process and the trial process. From these stages, an estimate of the processing time and cost of the Holing Machine manufacturing process can be obtained. With the creation of this Holing Machine, it is expected to reduce the waste of time in the hole making process on the Tube AC ​​Connecting K25G product by up to 22.59% from the previous hole making process time of 49.31% so that the waste of time in the production process of the Tube AC ​​Connecting K25G product can be reduced. That way, the productivity of making the Tube AC ​​Connecting K25G product can be increased.